ORAL MUCOSA: STRUCTURE, FUNCTIONS AND CLINICAL SIGNIFICANCE (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The oral mucosa is a specialized biological tissue that lines the oral cavity and plays a crucial role in maintaining oral and systemic health. It serves as a protective barrier against mechanical, chemical, and microbial insults while participating in sensory perception, immune defense, and tissue repair. The structure of the oral mucosa varies according to its location and function, resulting in different histological and physiological characteristics. Understanding the anatomy and functions of the oral mucosa is essential for the diagnosis and management of numerous oral diseases. This review summarizes current knowledge regarding the structure, functions, and clinical significance of the oral mucosa, emphasizing its role in oral pathology and modern dental practice.
Keywords: Oral mucosa, oral epithelium, oral cavity, histology, oral diseases, oral pathology, oral health, dentistry.